2018
DOI: 10.1097/md.0000000000012361
|View full text |Cite
|
Sign up to set email alerts
|

Clinical course and treatment outcomes of toxocariasis-related eosinophilic disorder

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
27
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 29 publications
3
27
0
4
Order By: Relevance
“…Therefore, they are often discovered during the investigation of eosinophilia, as in this study, and they are usually self-remitting regardless of treatment. Yoon et al reported that albendazole treatment and duration of albendazole treatment did not induce a significant difference in the improvement of eosinophilia between the treated and untreated groups of toxocariasis patients [7]. Therefore, they suggested that anthelminthic therapy is not required except for in specific clinical situations, including ocular involvement [7].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, they are often discovered during the investigation of eosinophilia, as in this study, and they are usually self-remitting regardless of treatment. Yoon et al reported that albendazole treatment and duration of albendazole treatment did not induce a significant difference in the improvement of eosinophilia between the treated and untreated groups of toxocariasis patients [7]. Therefore, they suggested that anthelminthic therapy is not required except for in specific clinical situations, including ocular involvement [7].…”
Section: Discussionmentioning
confidence: 99%
“…Yoon et al reported that albendazole treatment and duration of albendazole treatment did not induce a significant difference in the improvement of eosinophilia between the treated and untreated groups of toxocariasis patients [7]. Therefore, they suggested that anthelminthic therapy is not required except for in specific clinical situations, including ocular involvement [7]. However, it is recommended to treat eosinophilia patients when they are diagnosed with toxocariasis, as the larvae can migrate to vital organs, including the eyes and brain, leading to severe sequelae.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Eosinophilia, on the other hand, has long been recognized as an important biomarker for toxocariasis [ 37 , 38 , 39 , 40 ]. In the major clinical presentation, visceral larva migrans (VLM) syndrome, eosinophilia is a distinguishable biomarker that can be drastically elevated [ 37 , 41 ].…”
Section: Discussionmentioning
confidence: 99%